Optimasi Manajemen Risiko dan Efektivitas Pengiriman Kargo: Uji Mediasi Service Quality dengan PLS-SEM pada CV Anugrah Alam Abadi - Putri Indah Lestari; Andri Soemitra; Tri Indah Fadhila Rahma (Politeknik Ganesha Medan, 2025)
The cargo distribution industry in Indonesia continues to face challenges such as lost, damaged, delayed, and exchanged goods. This study aims to analyze the effect of Risk Management Optimization on Cargo Distribution Delivery, with Service Quality as a mediating variable. Using a quantitative approach and the Structural Equation Model (SEM) method based on Partial Least Square (PLS), data were collected from 50 respondents consisting of 40 operational employees and 10 active customers of CV Anugrah Alam Abadi. The results show that Risk Management Optimization significantly influences Cargo Distribution Delivery (? = 0.565; p < 0.001) both directly and indirectly through Service Quality (? = 0.337; p = 0.006). These findings confirm that effective risk management not only reduces operational risks but also enhances service reliability and delivery efficiency. Practically, companies should strengthen Standard Operating Procedures (SOP) for cargo loading–unloading, implement real-time tracking systems, and establish clear Service Level Agreements (SLA) with transportation partners to minimize risk and improve customer satisfaction.